Validated Interpersonal Confidence Questionnaire to Measure the Impact of Improvisation Training - Seppänen Sirke; Novák Johanna; Toivanen Tapio; Tiippana Kaisa (United Kingdom, 2022)
Theatre-based improvisation includes a model of constructive communication, which has been applied to education, and in fields requiring interpersonal competencies. Here, we present a validation study of the Interpersonal Confidence Questionnaire (ICQ) developed to measure self-reported interpersonal confidence, that is, beliefs regarding one’s capability related to effective social interactions. Confirmatory factor analysis (n = 208) confirmed the 18-item measurement model of ICQ as satisfactory, with six factors contributing to interpersonal confidence: performance confidence, flexibility, listening skills, tolerance of failure, collaboration motivation, and presence. The questionnaire showed discriminatory power, acceptable composite reliability, and strong test–retest reliability. The immediate and long-term impact of six improvisation interventions (n = 161) were measured using ICQ. Improvisation interventions resulted in improvements to interpersonal confidence, performance confidence, and tolerance of failure relative to controls, and an improved performance confidence persisted over time. This study provides initial evidence on the validity and reliability of the 18-item, 6-factor ICQ as a self-report measurement of interpersonal confidence, which may increase following improvisation training.
ICEEPSY 2021 - International Conference on Education and Educational Psychology : Selected, peer reviewed papers from 12th International Conference on Education and Educational Psychology (ICEEPSY 2021), 06-08 October, 2021, Online